Naming Our World, Claiming Our Knowledge: Research-in-Practice in Adult Literacy Programs - Quigley, B. Allan (Alberta Journal of Educational Research, 1999)
Throughout its history adult literacy education has been defined, described, researched, and effectively controlled by external entities. This article discusses how literacy practitioners and learners are gaining a voice through the production of their own knowledge using research-in-practice. It especially examines the applicability, benefits, and inherent risks of practitioner action research, provides a discussion of how this research paradigm is defined, and concludes with possibilities for the future.